Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2007)
This paper provides a semi-annual review of the status of financing for PRGF-ESF lending, HIPC and MDRI debt relief, and subsidization of emergency assistance to PRGF-eligible members. The last review was completed by the Executive Board on April 13, 2007.